Effect of Angora Goat Age and Growing Season on the Frequency Distribution Shapes of Different Types of OFDA Measured Medullated Fibres in Commercial Mohair Sale Lots - Lawrance Hunter; Anton F. Botha (Journal of Natural Fibers, 2025)
A previous paper reported on the inter-relationships between Angora goat age, the average levels of different types of medullated fibers, mean fiber diameter and diameter variability for over 1400 mohair commercial sale lots, representative of different growing seasons (Winter and Summer of 2010 and 2015, respectively). It did not, however, address the question of the type and shape of the frequency distribution of the different types of medullated fibers, as measured by OFDA100. In view of this, and the complete lack of published information in this specific field, it was decided to fill this gap. This paper reports on the effect of goat age and season on the various types and shapes, in terms of normality, skewness and kurtosis, of medullated fiber frequency distribution, as opposed to average values, of the same commercial sale lots reported on previously. For the mean fiber diameter distributions, except for the Summer Kid mohair samples, the distributions were all statistically Normal. This was not the case for the distributions of the various types of medullated fibers which, with a few exceptions, deviated statistically significantly from Normal, the main exception being the Normal Medullated Fiber distributions for the Winter Kid and Adult hair.